Fintech and macroeconomi variables: Empirical evidence from panel data - Aini Azieta, Azizan (2019)
Fintech is a mixture of imaginative action plans and innovation that have a negative and positive impact on the services or financial product when implemented in the framework. For two decades, progress in the field of information technology (IT) has also been fundamental a reality for the ongoing application and dissemination of the Internet and online enterprises. The main motivation of this research is to identify the relationship between Fintech and macroeconomic variables towards economic growth. It is crucial to fully understand the relationship between financial technology and economic growth in order to determine the growth factor and on the other hands to determine the investment allocation to this type of telecommunication infrastructure. Hence, this study aims to disentangle the possible significant relationships between fintech with economic growth. The objective of the research will be employed by using by panel data from ten countries for year 1998-2017. In order to answer the objective of this research, the method to be employed is panel ordinary least squares (POLS) which to estimate how dependent variable reacts when there is an increase in independent variables, granger causality test is to determine the direction of causality between all variable and Pedroni cointegration test to determine the existence of cointegration between the variables in the long run equilibrium. Based on empirical findings, there does exist a long relationship between fintech and the economic growth. Besides that the estimated result show that other independent variables such as mobile user exist bidirectional causality with fintech in the long run meanwhile it exist unidirectional causality relationship between broadband and mobile user. Furthermore, in Pedroni cointegration test confirmed that there is existence of cointegration among the selected variables. In other word there have long run equilibrium between mobile user, broadband, import, export and inflation with economic growth. In order to adopting financial technology across the countries the regulator must ensure that more information technology infrastructure is built, such as providing additional infrastructure in conjunction with current needs and encouraging people to work with Fintech by highlighting the benefits they can gain by using the technology. Furthermore, the government can grant subsidies to network suppliers to build more mobile cellular networks and increase the line coverage particularly in rural areas and equally increase in the use of Fintech